La théorie des imaginaires de la traduction - Christina Bezari; Riccardo Raimondo; Thomas Vuong (Itinéraires)
A translation can not be read only as a clear and unidirectional exchange of signs, where one could automatically replace an other. The idea of imaginaries allows the critic to shed light on translating choices, on the one hand by studying the representations and preconceptions of the very act of translating a text (the imaginaries of translating), on the other hand by delving into every factor—be it explicit or implicit, personal or collective—that have influenced and shaped any translator’s work (the imaginaries of translators). A hybrid concept which draws from social sciences, psychology or aesthetics, the imaginary becomes a new tool among the translation scholar’s toolbox. Moreover, it also constitutes a method that allows to find new paths into intercultural studies, hermeneutics, literary history, so far as to allow to isolate recurring patterns of translation, which may help sketching a mapping of translation phenomenons. It is also a way to bind further the comparatist and translation studies approaches of themselves.